"Doing it" for the right reasons: Validation of a measurement of intrinsic motivation, extrinsic motivation, and amotivation for sexual relationships. (April 2016) - Gravel, Emilie Eve; Pelletier, Luc G.; Reissing, Elke Doris
Abstract: This investigation examined the psychometric properties of the Sexual Motivation Scale (SexMS), a scale measuring the different types of self-regulation proposed by SDT in the context of sexual relationships: Intrinsic motivation, extrinsic motivation, and amotivation. We analyzed the construct validity of the SexMS in two studies (Study 1: N = 1070, Study 2: N = 575). Results from a confirmatory factor analysis indicated that the SexMS can adequately reproduce the correlated six-factor structure posited by SDT. Findings from measurement invariance analyses as a function of gender and relationship type (i.e., casual and committed), tests for internal consistency, and correlational analyses all provided support for the reliability and the validity of the SexMS. Importantly, self-determined sexual regulation was associated to positive sexual health and well-being outcomes, whereas the inverse was found for non-self-determined sexual regulation. Additionally, participants who scored within the problematic range of sexual function showed a greater endorsement of non-self-determined sexual regulation and a lower endorsement of self-determined sexual regulation than those who scored in the non-problematic range. Overall, the SexMS provides a valuable tool to investigate sexuality within a SDT framework and a fine-grained measurement for the examination of the motivational processes associated with sexual health and well-being. Highlights: We developed a measure of sexual motivation grounded in self-determination theory. The measure shows good factorial validity, with six correlated factors. The subscales display good internal consistency and discriminant validity. This instrument can detect important variations in sexual health and well-being.